Decision-Making Processes in Conflict Resolution among Air Traffic Controllers (ATCOs) during Aircraft Arrivals - Sherrie Winer, Anthony; Hana, Hamidi; Victoria, Jonathan (HRMARS, 2024)
Decision-making processes is an important topic especially among Air Traffic Controllers (ATCOs) as they need to make decisions in a very dynamic environment. Managing air traffic can be quite challenging for them. This study aims to provide valuable insights into the decision-making processes of ATCOs within the Malaysia context, an area with limited prior research. Using the Generalized ATC Model, this research contributes to the model through empirical data and existing literature. This research specifically investigates the decision making processes involved in conflict resolution among ATCOs, with a particular focus on adverse weather conditions during aircraft arrivals. The study also examines the workload ATCOs experience during these decision-making processes and how they manage that stress. Data were collected using three methods: semi-structured interviews with 12 informants, observations, and document analysis. The findings revealed that decision-making starts with area controllers monitoring aircraft, followed by approach controllers who sequence the aircraft based on specific criteria, and aerodrome controllers granting landing clearance. In relations with that, the findings have major implications for improving training and development of the ATCOs. The insights derived from this research can guide the training needs analysis (TNA) process conducted by HR departments to enhance ATCOs’ decision making capabilities in managing aircraft arrivals. Other than that, future researchers are encouraged to conduct mix method research by employing both qualitative and quantitative methods to different geographical locations, such as the Civil Aviation Authority of Malaysia (CAAM) in Peninsular Malaysia which can offer valuable comparative insights into decision making practices among ATCOs across diverse contexts.